Deformation partitioning in mountain belts: insights from analogue modelling experiments and the Taiwan collisional orogen. (11th January 2021) - Malavieille, Jacques; Dominguez, Stephane; Lu, Chia-Yu; Chen, Chih-Tung; Konstantinovskaya, Elena
Abstract: Many orogens on the planet result from plate convergence involving subduction of a continental margin. The lithosphere is strongly deformed during mountain building involving subduction of a plate composed generally of accreted continental margin units and some fragments of downgoing oceanic crust and mantle. A complex deformation involving strong partitioning of deformation modes and kinematics produces crustal shortening, accompanied by crustal thickening. Partitioning depends on three main factors: (1) rheologic layering of the lithosphere; (2) interaction between tectonics and surface processes; (3) subduction kinematics and 3D geometry of continental margins (oblique convergence, shape of indenters). Here we present an original view and discussion on the impact of deformation partitioning on the structure and evolution of orogens by examining the Taiwan mountain belt as a case study. Major unsolved questions are addressed through geological observations from the Taiwan orogen and insights from analogue models integrating surface processes. Some of these questions include: What is the role played by décollements or weak zones in crustal deformation and what is the impact of structural heterogeneities inherited from the early extensional history of a rifted passive continental margin? What is the relationship between deep underplating, induced uplift and flow of crustal material during erosion (finite strain evolution during wedge growth)? Are syn-convergent normal faults an effect of deformation partitioning and erosion? What is the role of strain partitioning on the location of major seismogenic faults in active mountain belts? What can be learned about the long-term and the present-day evolution of Taiwan?